MSME EMPOWERMENT POLICY STRATEGY IN ORDER TO DO ACCELERATING OF THE DEVELOPMENT FINANCIAL SERVICES ECOSYSTEM - Tri Handayani; Lastuti Abubakar (Trunojoyo Madura University, 2022)
The post-Covid-19 National Economic Recovery (PEN) is carried out through the synergy of the Government's policies with the Financial Services Authority (OJK), one of which is regarding financing for the Priority Economic Sector, namely MSMEs. The government issued a PEN policy in order to protect, maintain and improve the economic capacity of business actors during the pandemic. On the other hand, OJK is committed to encouraging the development of MSMEs so that they become a buffer for the economy. OJK's steps are committed to maintaining financial system stability. In implementing the policy, of course, there will be challenges and obstacles, therefore the legal issue that will be studied is how the policy strategy can be applied in terms of developing MSMEs in order to realize a financial services ecosystem. The research method used is a normative juridical approach using secondary data in the form of primary legal materials, namely legislation, secondary legal materials, namely journal articles and the results of previous research. Primary data is the result of research conducted using a legal approach, namely through a review of all laws and regulations related to the legal issues being studied. The results of the analysis show that the empowerment of MSMEs in the context of Accelerating the Development of the Financial Services Ecosystem begins with the issuance of policies by the government, namely: the National Recovery Program, the Implementation of the Job Creation Act and its derivative regulations, as well as the Indonesian-made Proud Movement program. In addition, steps to suspend the settlement of MSME obligations or debts for both tax obligations and business loan obligations, and provide loans directly to MSME actors so that they can have sufficient capital to maintain business and encourage the digitization of MSME businesses so that they can continue to operate in conditions where there are social restrictions. Community is a step that is considered to save the existence of MSMEs during the Pandemic.